TEXNOLOGIYA DARSLARIDA O‘QUVCHILARNING TEJAMKORLIK XISLATLARINI SHAKLLANTIRISH ORQALI INSONPARVARLIKNI RIVOJLANTIRISH (International conference on multidisciplinary science, 2026)
This thesis addresses the issues of developing humanistic qualities in students by forming economical skills during technology lessons. It analyzes the pedagogical opportunities for fostering the rational use of resources, a conscious attitude toward labor, and social responsibility within the educational process.